Use of Implantable Loop Recorders to Unravel the Cause of Unexplained Syncope - Puri, Aniket (Indian Heart Rhythm Society, 2013)
Syncope is a symptom of many underlying disease states, which range from the relatively benign to the life threatening. There are numerous investigations done for patients with recurrent unexplained syncope which may have very low yield when it comes to making a definitive diagnosis. Recently, the implantable loop recorder (ILR) for continuous monitoring of the cardiac rhythm has been launched in India. This review will briefly discuss these current available strategies and focus on the usefulness of an ILR in the definitive diagnosis and treatment of patients with a recurrent unexplained syncope.